Pelecehan Seksual Terhadap Anak Di Bawah Umur Dalam Persfektif Hukum Islam Dan Hukum Pidana - Muhammad Ridwan Lubis (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
Abstract The prohibition of khalwat (or lewd acts) as the enforcement of the Islamic rules and customs among people in Nangroe Aceh Darussalam Province is to protect the community from various forms of destructive activities or deeds, to prevent the people as early as possible from committing adultery, to increase community participation, to prevent and eradicate the occurrence of khalwat (or lewd acts), and to close the opportunity for moral damage. The law enforcement apparatus found obstacles to settle the khalwat cases; consequently, the case was not transferred to the Syar'iyah Court (a court based on Islamic rules). The constraints of the difference to categorize khalwat (or lewd act) are due to the customary law that still prevails in society, the imperfect law, lack of wilayatul hisbah officers (Islamic law enforcers), lack of legal awareness and knowledge, and environmental factors.